Multiparameter Biosignal Analysis in Elderly Ischemic Stroke Patients - Muhammad Zakariyah; Alvin Sahroni; Erlina Marfianti (Journal of Biomedical Science and Bioengineering, 2021)
Biosignal can provide information about body conditions, including physiological conditions of ischemic stroke. The regulation of blood in the brain is regulated through the mechanism of Cerebral Autoregulation (CA). Some parameters that can be used to determine this mechanism are Blood Flow Velocity (BFV) and Blood Pressure (BP). Stroke is also related to nervous system activity, which is represented through the Heart Rate Variability (HRV). This study aims to determine the relationship between those biosignals and their effects on the physiology of ischemic stroke sufferers. The subjects were divided into two groups (20 strokes and 20 controls). BFV data is obtained in the Middle Cerebral Artery (MCA), BP is obtained through the arteries of the upper arms, and 3 leads electrocardiogram is placed in the chest. The results showed that there was a relationship between BP and BFV in the control group (p-value < 0.05; r = -0.574). This correlation was not found in the stroke group. The relationship between BP and HRV was only found in the stroke group, which was associated with high sympathetic activity and lower parasympathetic activity (p-values < 0.05 and r > 0.4). It was based on SDRR, RMSSD, CVRR, LF, and SD1 parameters. In the control group, there was no relationship between HRV and BP. The relationship between BFV and HRV in the control group was not found statistically. Still, in the stroke group, this relationship was found in the LF and LF/HF Ratio parameters (p-value < 0.05; r > 0.4). Based on this research, parameters on HRV that can be used to determine the characteristics of stroke patients in all positions are MeanRR, VLF, and LF